2019
DOI: 10.1002/jso.25757
|View full text |Cite
|
Sign up to set email alerts
|

Full axillary lymph node dissection and increased breast epidermal thickness 1 year after radiation therapy for breast cancer

Abstract: Background We previously reported a prospective study showing axillary lymph node dissection (ALND) is associated with increased breast skin thickening during and 6 weeks post‐radiation therapy (RT), and now report ALND's long‐term impact at 1 year. Methods Among 66 women who received whole breast RT after lumpectomy, objective ultrasound measurements of epidermal thickness over four quadrants of the treated breast were measured at five time points: before RT, week 6 of RT, and 6 weeks, 6 months, and 1 year po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The selected studies were published between 1998 and 2021 and were geographically diverse, representing eight countries. A total of 6/17 studies were conducted in the same centre in the USA (Emory University School of Medicine), almost by the same group of authors [ 9 , 31 , 32 , 33 , 34 , 35 ]. One of these studies [ 9 ] was a more comprehensive follow-up study with 77% of the patients from the previous one [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selected studies were published between 1998 and 2021 and were geographically diverse, representing eight countries. A total of 6/17 studies were conducted in the same centre in the USA (Emory University School of Medicine), almost by the same group of authors [ 9 , 31 , 32 , 33 , 34 , 35 ]. One of these studies [ 9 ] was a more comprehensive follow-up study with 77% of the patients from the previous one [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 6/17 studies were conducted in the same centre in the USA (Emory University School of Medicine), almost by the same group of authors [ 9 , 31 , 32 , 33 , 34 , 35 ]. One of these studies [ 9 ] was a more comprehensive follow-up study with 77% of the patients from the previous one [ 32 ]. Lastly, three studies were conducted by the same author in Newcastle Mater Hospital, Waratah, NSW, Australia [ 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In women with bosom malignant growth who go through bosom rationing a medical procedure [1], [2], entire bosom illumination diminishes the danger of neighborhood repeat and forestall requirement for mastectomy [3]- [5]. An upgradation of a meta-investigation showed that bosom light after bosom saving a medical procedure lessens mortality from bosom cancer [6], [7] However, up to 30% of ladies in North America who go through bosom preserving a medical procedure do not go through bosom illumination, partially in view of the burden of the treatment and its cost [7], [8].…”
Section: Introductionmentioning
confidence: 99%